Effects of frankincense on experimentally induced renal stones in rats - Mohamed S. Al‐Marhoon; Ahmed Al‐Harrasi; Khurram Siddiqui; Mohammed Ashique; Haytham Ali; Badreldin H. Ali (BJUI Compass, 2023)
Abstract Objectives Frankincense (Luban) is a resin obtained from trees of genus Boswellia. The south of Oman hosts Boswellia sacra trees known to have many social, religious and medicinal uses. The anti‐inflammatory and therapeutic potential of Luban has recently attracted the interest of the scientific community. The aim is to study the efficacy of Luban water extract and its essential oils on experimentally induced renal stones in rats. Materials and Methods A rat model of urolithiasis induced by trans‐4‐hydroxy‐L‐proline (HLP) was used. Wistar Kyoto rats (27 males, 27 females) were randomly distributed into nine equal groups. Treatment groups were given Uralyt‐U (standard) or Luban (50, 100 and 150 mg/kg/day), starting Day 15 from HLP induction for a duration of 14 days. The prevention groups were given Luban in similar doses, starting Day 1 of HLP induction for 28 days. Several plasma biochemical and histological parameters were recorded. Data were analysed with GraphPad Software. Comparisons were performed by one‐way analysis of variance (ANOVA) and the Bonferroni test. Results The lithogenic effects of HLP, such as an increase in urine oxalate and cystine, an increase in plasma uric acid and an increase in kidney levels of calcium and oxalate, have all been best significantly reversed by the Luban dose of 150 mg/kg/day. The histological changes of HLP on the kidney tissue including calcium oxalate crystal formation, cystic dilatation, high degree of tubular necrosis, inflammatory changes, atrophy and fibrosis have also been ameliorated by Luban dose of 150 mg/kg/day. Conclusion Luban has shown a significant improvement in the treatment and prevention of experimentally induced renal stones, particularly at a dose of 150 mg/kg/day. Further studies on the effect of Luban in other animal models and humans with urolithiasis are warranted.